A fast response, self-powered and room temperature near infrared-terahertz photodetector based on a MAPbI3/PEDOT:PSS composite. Issue 35 (11th August 2020) - Li, Yifan; Zhang, Yating; Li, Tengteng; Tang, Xin; Li, Mengyao; Chen, Zhiliang; Li, Qingyan; Sheng, Quan; Shi, Wei; Yao, Jianquan
Abstract : A novel self-powered NIR and THz PTE PD based on a (MAPbI3 /PEDOT:PSS) composite with a rapid response time of 28 μs. Abstract : Organic–inorganic halide perovskites with low thermal conductivity, high Seebeck coefficients and high carrier mobilities are promising thermoelectric materials for near infrared (NIR) and terahertz (THz) photodetectors (PDs). Here, we report a novel rapid response and self-powered NIR and THz photothermoelectric PD based on a CH3 NH3 PbI3 (MAPbI3 ) and poly(3, 4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) composite. An order of magnitude enhancement in the Seebeck coefficient was observed that resulted from the addition of PEDOT:PSS. Under 1064 nm and 2.52 THz illumination, the device displays a stable and repeatable photoresponse at room temperature under a zero bias voltage. The frequency response shows a −3 dB frequency band of 5 kHz, corresponding to a fast response time of 28 μs, which is approximately three orders of magnitude faster than the previously reported results. These results demonstrate that MAPbI3 /PEDOT:PSS is a promising composite material for fast response and self-powered NIR-THz PTE PDs operating at room temperature.